Semantics and poetics of the motif of voice in Gaito Gazdanov’s 1920-30 small prose: “Transformation” and “The disappearance of Ricardy” - Євстаф’єва, Наталія Павлівна; Чорна, Карина Юріївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2020)
The article is dedicated to research of the motif of voice in the semantic structure of Gaito Gazdanov’s 1920–30 small prose. Stories, representing the author’s intentional object in his early works, were considered. The use of the methods of motif and intermedial analysis has made it possible to establish that dynamics of the stories’ “Transformation” and “The disappearance of Ricardy” plot is connected with the paradigm of metaphysic existence. The main components of this paradigm are translated into auditory imageries in Gazdanov’s narrative. A study of the texts has shown that during multiple variations audial imageries become motifs that mark existential-ontological problematics of works and form multifaceted art space. The motif of voice is highlighted as one of the main carriers of meaning in the motif system of both stories, which explicate the processes of consciousness of narrating subject and endowed with function of other character attributes. The motif of voice is also a dominant element of the intermedial code. Author’s intermedial strategies are reflected through the references to “Elegy” by a French composer J. Massenet (“Transformation”) and to vocal and instrumental performances of crossover music textes, decoding the collision of opera singer Ricardy (“The disappearance of Ricardy”). Ultimately, both of Gazdanov’s stories are considered to be a testimony to the acceptance of inevitability of human existence in two planes of being: ontologically possible and empirically given. The art strategy of audial writing has proven to be the most productive way to objectify this type of author’s consciousness in the writer’s early prose. The next stages of Gazdanov’s art system evolution are also marked by the author’s great focus on the potential of audial and intermedial narration techniques. It offers the clear prospect of studying them as dynamical integrity.